ANALYSIS OF DIFFERENCES IN BODY WEIGHT AND BODY LENGHT IN INFANTS AGE 6-7 MONTHS BETWEEN EXCLUSIVE BREASTFEEDING THE WORK AREA OF KOTA BARAT HEALTH CENTER - Harismayanti Harismayanti; Ani Retni; Siti Nurain Dunggio (Jambura Journal of Health Sciences and Research, 2023)
Rendahnya cakupan ASI Ekslusif merupakan sebuah masalah kesehatan di Indonesia. Hasil Riset Kesehatan Provinisi Gorontalo, cakupan ASI eksklusif sebanyak 64% dengan target  nasional yaitu 80% sehingga dapat dilihat bahwa cakupan ASI di Gorontalo belum mencapai target yang sudah ditetapkan. Kebaruan penelitian ini karena menganalisis perbedaan berat badan dan panjang badan pada bayi usia 6-7 bulan yang di berikan ASI Ekslusif di wilayah kerja puskesmas Kota Barat. Tujuan dalam penelitian ini adalah menganalisis perbedaan berat badan dan panjang badan pada bayi usia 6-7 bulan yang diberikan ASI Ekslusif. Metode penelitian ini menggunakan desain survey analitik dengan melalui pendekatan cross sectional study. Sampel diambil dengan teknik accidental sampling pengambilan dengan jumlah sampel 40. Pengumpulan data menggunakan lembar kuesioner dan obervasi. Analisis data menggunakan uji Chi Square dengan tingkat kemaknaan (Î±=0,05). Hasil penelitian berdasarkan uji statistik didapatkan nilai p value=0,030 dengan Î± 0,05, sehingga ada hubungan antara pertumbuhan berat badan bayi yang diberi ASI eksklusif dan tidak ASI eksklusif, dan didapatkan nilai p value=0,212 dengan Î± 0,05, sehingga tidak ada hubungan antara pertumbuhan panjang badan bayi yang diberi ASI eksklusif dan tidak ASI eksklusif di wilayah kerja Puskesmas Kota Barat. Kesimpulan penelitian ini yakni ada hubungan antara pertumbuhan berat badan bayi yang diberi ASI eksklusif dan tidak ASI eksklusif dan tidak ada hubungan antara pertumbuhan panjang badan bayi yang diberi ASI eksklusif dan tidak ASI eksklusif di wilayah kerja Puskesmas Kota Barat.Kata Kunci: ASI Eksklusif; Berat Badan Bayi; Panjang Badan Bayi.AbstractThe low coverage of exclusive breastfeeding is a health problem in Indonesia. The results of the Gorontalo Provincial Health Research show that the range of exclusive breastfeeding is 64%, with a national target of 80%, so it can be seen that the coverage of breastfeeding in Gorontalo has not reached the mark that has been set. The novelty of this study is that it analyzes differences in body weight and length in infants aged 6-7 months who are given exclusive breastfeeding in the working area of the West City Health Center. The aim of this study was to analyze differences in body weight and length in infants aged 6-7 months who were given exclusive breastfeeding. This research method uses an analytic survey design with a cross-sectional study approach. Samples were taken by accidental sampling technique with a total sample of 40. Data were collected using questionnaires and observations. Data analysis used the Chi-Square test with a significance level (Î±=0.05). The results of the study based on statistical tests obtained a p-value = 0.030 with Î± 0.05, so there is a relationship between the weight growth of babies who are exclusively breastfed and those not exclusively breastfed, and a p-value = 0.212 is obtained with Î± 0.05, so there is no relationship between the growth in body length of babies who are exclusively breastfed and not exclusively breastfed in the working area of the West City Health Center. This study concludes that there is a relationship between the growth in body weight of babies who are exclusively breastfed and not exclusively breastfed, and there is no relationship between the body length growth of babies who are exclusively breastfed and not breastfed solely in the working area of the Kota Barat Health Center.